Causal Control of Medial–Frontal Cortex Governs Electrophysiological and Behavioral Indices of Performance Monitoring and Learning - Reinhart, Robert M. G.; Woodman, Geoffrey F. (The Journal of neuroscience, 2014)
Adaptive human behavior depends on the capacity to adjust cognitive processing after an error. Here we show that transcranial direct current stimulation of medial–frontal cortex provides causal control over the electrophysiological responses of the human brain to errors and feedback. Using one direction of current flow, we eliminated performance-monitoring activity, reduced behavioral adjustments after an error, and slowed learning. By reversing the current flow in the same subjects, we enhanced performance-monitoring activity, increased behavioral adjustments after an error, and sped learning. These beneficial effects fundamentally improved cognition for nearly 5 h after 20 min of noninvasive stimulation. The stimulation selectively influenced the potentials indexing error and feedback processing without changing potentials indexing mechanisms of perceptual or response processing. Our findings demonstrate that the functioning of mechanisms of cognitive control and learning can be up- or down-regulated using noninvasive stimulation of medial–frontal cortex in the human brain.